2017
DOI: 10.1007/s40262-017-0536-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Novel Formulation of Abiraterone Acetate vs. the Originator Formulation in Healthy Male Subjects: Two Randomized, Open-Label, Crossover Studies

Abstract: Background and ObjectiveAbiraterone acetate is approved for the treatment of metastatic castration-resistant prostate cancer. The originator abiraterone acetate (OAA) formulation is poorly absorbed and exhibits large pharmacokinetic variability in abiraterone exposure. Abiraterone acetate fine particle (AAFP) is a proprietary formulation (using SoluMatrix Fine Particle Technology™) designed to increase the oral bioavailability of abiraterone acetate. Here, we report on two phase I studies in healthy male subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 9 publications
(12 reference statements)
0
18
0
Order By: Relevance
“…The recently published work of Goldwater et al confirmed that a single 500 mg dose of AAFP prepared using SoluMatrix Fine Particle Technology ™ was bioequivalent with the 1000 mg Zytiga dose under fasted conditions [9]. The geometric mean of test: reference (90% confidence interval limits) were 91 (83.3 to 99.4) and 99.8 (86.3 to 115.5) for AUC inf and C max , respectively [9].…”
Section: Abirateronementioning
confidence: 95%
See 2 more Smart Citations
“…The recently published work of Goldwater et al confirmed that a single 500 mg dose of AAFP prepared using SoluMatrix Fine Particle Technology ™ was bioequivalent with the 1000 mg Zytiga dose under fasted conditions [9]. The geometric mean of test: reference (90% confidence interval limits) were 91 (83.3 to 99.4) and 99.8 (86.3 to 115.5) for AUC inf and C max , respectively [9].…”
Section: Abirateronementioning
confidence: 95%
“…Because there was the addition of methylprednisolone (4 mg twice daily) to AAFP or prednisone (5 mg twice daily) to the Zytiga tablets, there was the need of a single dose bioequivalence study to confirm the existence of bioequivalence of 500 mg AAFP versus 1000 mg Zytiga tablets [8]. The recently published work of Goldwater et al confirmed that a single 500 mg dose of AAFP prepared using SoluMatrix Fine Particle Technology ™ was bioequivalent with the 1000 mg Zytiga dose under fasted conditions [9]. The geometric mean of test: reference (90% confidence interval limits) were 91 (83.3 to 99.4) and 99.8 (86.3 to 115.5) for AUC inf and C max , respectively [9].…”
Section: Abirateronementioning
confidence: 99%
See 1 more Smart Citation
“…The higher surface area--to-mass ratio can increase the in vivo dissolution rate of lipophilic, poorly water-soluble, active pharmaceutical ingredients such as AA that often have dissolution rate-limited oral bioavailability. In a previous companion study of healthy male subjects, AAFP 500 mg was shown to be bioequivalent to OAA 1000 mg (within 80-125% of C max and AUC) when taken under fasted conditions [13]. The present study investigates the effect of a high-fat meal on AAFP pharmacokinetic parameters and bioavailability.…”
Section: Introductionmentioning
confidence: 91%
“…Based on a previous companion study, a sample size of 22 subjects was deemed sufficient to provide statistical power to detect a 20% difference in the reference mean between fed and fasted conditions [13]. Assuming a screen failure/dropout rate of 15%, enrollment of 26 subjects was planned.…”
Section: Statistical Analysesmentioning
confidence: 99%